Prevalence and risk factors for disability in leprosy patients in Indonesia during the post-elimination era (Dermatology Reports, 2023)
Leprosy has been nationally eliminated in Indonesia, but it continues to be a public health problem, with disability contributing to the disease burden. Disability caused by leprosy often results in stigmatization, leading to decreased quality of life. This was a retrospective cross-sectional study using secondary data from primary healthcare centers in one of the districts in the region with the highest number of leprosy patients in Indonesia. All leprosy patients between 2016-2022 were included. Among 189 leprosy patients (mean age 46 years old, 65.6% male), 19% had grade 1 disability and 29.6% had grade 2 disability. Duration of disease, nerve enlargements, leprosy reactions, and symmetric lesions were identified as risk factors for both grade 1 and 2 disability. Being male and having a positive smear test was associated with a higher risk of only grade 2 disability. Disability due to leprosy is still prevalent in the post-elimination era despite the decline in new leprosy cases. Improvement in early case detection and prevention of disability are still needed in the post-elimination era.